Portable Skin Analyzers with Simultaneous Measurements of Transepidermal Water Loss, Skin Conductance and Skin Hardness - Daniel (Jai Kyoung) Sim; Sung Mok Kim; Steve S. Kim; Il Doh (Sensors, 2019)
Simultaneous measurement of skin physiological and physical properties are important for the diagnosis of skin diseases and monitoring of human performance, since it provides more comprehensive understanding on the skin conditions. Current skin analysis devices, however, require each of probes and unique protocols for the measurement of individual skin properties, resulting in inconvenience and increase of measurement uncertainty. This paper presents a pen-type skin analyzing device capable tomeasure three key skin properties at the same time: transepidermal water loss (TEWL), skin conductance, and skin hardness. It uses a single truncated hollow cone (THC) probe integrated with a humidity sensor, paired electrodes, and a load cell for the multimodal assessment of the skin properties. The present device measured TEWL with a sensitivity of 0.0068 (%/s)/(g/m2/h) and a linearity of 99.63%, conductance with a sensitivity of 1.02 µS/µS and a linearity of 99.36%, and hardness with a sensitivity of 0.98 Shore 00/Shore 00 and a linearity of 99.85%, within the appropriate ranges for the human skin. The present pen-type device has a high potential for the skin health diagnosis as well as the human performance monitoring applications.